2022
DOI: 10.3389/fimmu.2022.877953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combination of Everolimus and Mesenchymal Stromal Cells on Regulatory T Cells Levels and in a Liver Transplant Rejection Model in Rats

Abstract: IntroductionMesenchymal stromal cells (MSCs) have particular properties that are of interest in organ transplantation, including the expansion of regulatory T cells (Tregs), a key factor in transplant tolerance induction. However, the most effective immunosuppressive drug to associate with MSCs has yet to be defined. Additionally, the impact of the association of everolimus with MSCs on Treg expansion, and on the induction of liver graft tolerance, has never been studied. The aim of this study was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…One study compared the therapeutic potential of MSCs from different origins in a mouse GVHD model and found that bone marrow-derived MSCs (BM-MSCs) induced a rapid proinflammatory response before exerting immunosuppressive effects and that BM-MSCs were less capable of inducing Treg differentiation than umbilical cord blood-derived MSCs (UC-MSCs)[ 31 ]. Therefore, differences in the origin of MSCs might be a reason why some MSCs did not exert the expected effects in some studies[ 7 , 8 ]. It has also been suggested that subsequent studies on MSCs may focus on the differences in the therapeutic potential of MSCs that are derived from different sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study compared the therapeutic potential of MSCs from different origins in a mouse GVHD model and found that bone marrow-derived MSCs (BM-MSCs) induced a rapid proinflammatory response before exerting immunosuppressive effects and that BM-MSCs were less capable of inducing Treg differentiation than umbilical cord blood-derived MSCs (UC-MSCs)[ 31 ]. Therefore, differences in the origin of MSCs might be a reason why some MSCs did not exert the expected effects in some studies[ 7 , 8 ]. It has also been suggested that subsequent studies on MSCs may focus on the differences in the therapeutic potential of MSCs that are derived from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of another clinical study showed that the infusion of MSCs into liver transplant recipients before surgery was safe, but only mild changes in the peripheral blood immunoregulatory T cell numbers and natural killer cell numbers were observed in these patients[ 7 ]. In addition, the administration of immunosuppressive agents with MSCs showed no synergistic effect compared with the administration of immunosuppressive agents alone in a rat liver transplant study[ 8 ]. Therefore, approaches that enable MSCs to exert more significant protective effects in reducing IRI and inducing immune tolerance in liver transplantation deserve further study.…”
Section: Introductionmentioning
confidence: 99%